Consumer Entitlement Inventory: A Scale Extension and Application to the Vietnamese Retail Context - Van Nguyen, Si; Vo, Minh (Organizations and Markets in Emerging Economies, 2021)
The consumer entitlement (CE) construct is a key variable in the exchange process in retail environments. The original Consumer Entitlement Inventory (CEI) was developed and applied within Western cultural boundaries. The main contribution of this study is the extension of the original CEI to better fit the Vietnamese context and to demonstrate its applicability in the context of an emerging economy with a Confucian culture. The study also contributes to expanding the range of identified boycott motives in the literature and clarifying their mechanism via social exchange theory. The extended CEI scale was tested using exploratory factor analysis and confirmatory factor analysis, using a sample of 603 respondents. Qualitative and quantitative research results show that the extended CEI has two dimensions, namely intransigence, and demand and distinction, with adequate content, reliability, convergent validity, and discriminant validity. This study also aimed to apply the extended CEI to an exploration of the relationship between CE and willingness to boycott. Research results from another independent study with 450 respondents using a structural equation model confirmed the positive relationship between CE and willingness to boycott. In addition, theoretical implications are discussed.
Keywords: Consumer entitlement; social exchange theory,; willingness to boycott; Confucian culture; extended CEI